Genetic Diversity Among Carob Accessions from NW-Latakia (Syria) as Detected by RAPDs - Mahfoud, Hafez; Nasser, Samer; Amin, Talal (International Journal For Research In Agricultural And Food Science, 2018)
Fifteen RAPD primers were used to assess the genetic diversity and structure of 26 Syrian natural Ceratonia siliqua L. (Carob) accessions from four locations in NW-Latakia province. Atotal of 102 bands were obtained, 63 of which (61.74%) were polymorphic, with an average of 6.8 bands/primer. The percent of polymorphic bands within accessions from each location was calculated and it was highest within Al-Dakaka accessions (50.56%) while lowest was recorded in Um-Altueur (44.57%). The dendrogramme produced by Jaccard's coefficient and the UPGMA clustering method applied to the RAPD analysis shows four main groups with coefficient of dissimilarity values ranged from 0.05 to 0.25. The maximum dissimilarity percentage i.e. 25% was found between two accessions from Um Al-Tueur (T3, T8) and all other studied accessions, while the minimum similarity i.e. 5% was found between D2 and D3 from Al-Dakaka location.